Behavioral study of female crab Brytelphusa guerini under acute stress of dimethoate. - B, Deshai R; P, Katore B; D, Shinde V; E, Ambore N (International Multidisciplinary Research Journal, 2012)
Behaviour includes all those process by which an animal senses the external world and internal state of its body, and responds to changes which it perceives. Many of such processes will take place inside the nervous system and may not be directly observed but reflected through the behaviour of the animal. When an organism is exposed to any toxic agent, some changes occur in the behaviour which can be observed externally. These behavioral changes may be co-related to they changes occurring in the nervous system, as different behavioural responses are sub-served wholly or partly be the different neural circuits which are distributed in the nervous system. Earlier reports revealed that there is a strong correlation between physiological activities, metabolic changes and behaviour of animals. The paper deals with toxic effect of dimethoate on fresh water female crab Barytelphusa guerini and its behavioural study. The experimental animal shows various activities which is recorded and discussed.